A vámospércsi Farkasvölgye Vadásztársaság marketing tevékenységének az elemzése - Mán Ede Balázs (2015)
A dolgozatban bemutatásra kerül a társaság általános leírása, ökológiai, vadgazdálkodási és turisztikai tulajdonságai. Ezután a marketingeszközökről beszélek általánosan, majd a tár-saság marketing aktíváiról. Végül elemzésre kerül a társaság marketing tevékenysége és néhány ajánlás a marketingtevékenységek fejlesztésére. In this thesis, I’m going to introduce the general description of the association, ecological traits, hunting and related services and tourism. After this, I will talk about marketing tools in general, and the marketing assets of the association. Lastly, I will analyse the marketing activities of the association, I will make an offer for the development of some of these ac-tivities.